2017
DOI: 10.1001/jamainternmed.2017.1442
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Statin Treatment vs Usual Care on Primary Cardiovascular Prevention Among Older Adults

Abstract: IMPORTANCE While statin therapy for primary cardiovascular prevention has been associated with reductions in cardiovascular morbidity, the effect on all-cause mortality has been variable. There is little evidence to guide the use of statins for primary prevention in adults 75 years and older. OBJECTIVES To examine statin treatment among adults aged 65 to 74 years and 75 years and older when used for primary prevention in the Lipid-Lowering Trial (LLT) component of the Antihypertensive and Lipid-Lowering Treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
147
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(160 citation statements)
references
References 40 publications
5
147
0
8
Order By: Relevance
“…In a recently published post hoc analysis of the ALLHAT-LLT study,12 which included patients with both hyperlipidaemia and hypertension, the authors performed a subanalysis including 726 people aged 75 years or older (375 receiving pravastatin and 351 receiving usual care) and found no reduction in all cause mortality or in CVD. Our results in participants without type 2 diabetes are in line with those of the ALLHAT-LLT study.…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published post hoc analysis of the ALLHAT-LLT study,12 which included patients with both hyperlipidaemia and hypertension, the authors performed a subanalysis including 726 people aged 75 years or older (375 receiving pravastatin and 351 receiving usual care) and found no reduction in all cause mortality or in CVD. Our results in participants without type 2 diabetes are in line with those of the ALLHAT-LLT study.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a recent observational study suggests a significant survival advantage exists among older adults with ASCVD treated with high‐ versus moderate‐intensity statins, amplified at maximal doses of high‐intensity statins 20. On the other hand, a recent post hoc analysis from the ALLHAT‐LLT (Antihypertensive and Lipid‐Lowering Treatment to Prevent Heart Attack Trial) found a signal ( P =0.07) for possible increased all‐cause mortality among older adults treated with statins 7. These findings highlight the necessity for clinical trials to evaluate the efficacy and safety of statin therapy, including high‐intensity therapy, for both primary and secondary prevention of cardiovascular disease, specifically in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, concerns have been raised about the adverse effects of statins and polypharmacy as a reason not to treat older patients as aggressively as younger patients 1, 6. Although data are mixed for primary prevention after the age of 75 years,7 studies in older patients with atherosclerotic cardiovascular disease (ASCVD) suggest no attenuation of benefit. The 2013 American College of Cardiology (ACC)/American Heart Association (AHA) Guideline on the Treatment of Blood Cholesterol to Reduce Atherosclerotic Cardiovascular Risk in Adults acknowledges the limitations of existing data on older individuals and recommends individualizing the decision to initiate statins for primary prevention in adults >75 years 1.…”
mentioning
confidence: 99%
“…7 The report says that future controversies could be prevented through better communication and, among other things, better access to data. But the debate about statins in people at low risk has not gone away, [8][9][10][11] and the anonymised trial data remain inaccessible. The academy could have put its weight behind calls for an independent review of the evidence, 12 similar to the review on breast cancer screening commissioned by the UK's cancer tsar in 2012.…”
Section: Missed Opportunitiesmentioning
confidence: 99%